Developments in China’s Early Childhood Education in the Wake of the Institution of the Preschool Education Law of the People’s Republic of China - Yu, Haitao (Science Insights Education Frontiers, 2026)
The institution of the Preschool Education Law of the People’s Republic of China represents a milestone in the nation’s history of early childhood education. The law provides a legal framework for developing a generally accessible preschool education system, which is intended to span both urban and rural areas. This article gives a concise overview of the enactment of the law, delineates the improvements in pre-primary education in China as result of the law’s introduction, and highlights challenges of preschool education development in this country.